Progress in the fabrication of rare earth doped optical fiber by standard and Sol-Gel derived granulated oxides - Etissa, D.; Pilz, S.; Ryser, M.; Romano, V. (ALT Proceedings, 2026)
We produced active optical fibers by the doped granulate silica-method. The granulates were derived from the sol-gel technology. We determined volume percentage and distribution of chemical elements in the fabricated glasses fiber by the analytical technique of Energy-Dispersive X-ray (EDX), Scanning Electron Microscopy (SEM), Electron Probe Microanalysis (EPMA) and the degree of crystallization by X-Ray Diffraction analysis (XRD). Furthermore we measured fluctuations of the Refractive Index Profile (RIP) and scattering losses of the fiber core. It was observed from the RIP measurement that the average index difference with respect to the undoped silica was 5.3*10-3, and thus the optical fiber has a numerical aperture of 0.12. XRD measurements and investigations with SEM showed that the manufactured optical fiber has an amorphous structure. The dopant and co-dopant elements in the core region were uniformly distributed. Although we found strong isolated scattering centers in the fabricated fiber, the loss of the fibers was determined to be 0.35- 3dB/m for selected fiber pieces. Here we present our progress of improving the optical quality of fibers produced from granulates.